'Bharat' speaks out - "Joshi, Sharad" (Bombay, 1980)
Farmers' movements (as opposed to peasant strug gles, and the difference in terms is neither acciden tal nor merely semantic) have attracted considera ble attention in the country over the past few years. The movements in Karnataka, Tamil Nadu, Punjab and Maharashtra have been most noteworthy. The atmosphere, culture, standards of living, prob lems, issues and demands have been different in the urban and the rural areas for a long time. It would not however be true to say that the rural areas have not been a focus of concern of acti vists and intellectuals alike. Any discussions about development and poverty have necessarily embraced the situation of the rural masses. The attention received by the farmers' movement is hence not unprecedented. The current attention is however in some ways quite different. The main reason for this is that the contemporary farmers' movements. are movements of a new type.
Keywords: Peasantry India